SIMULATION OF WORST CASE TSUNAMI SCENARIO FROM THE MANILA TRENCH USING THE COMCOT MODEL - Phuong, Nguyen Hong; Phuong, Vu Ha; Truyen, Pham The; Vung, Vi Van (Vietnam Journal of Marine Science and Technology, 2014)
Among the tsunami source zones defined in the East Vietnam sea region, the Manila trench, west of the Philippines is considered as the most dangerous for the Vietnamese coast. The recent research results show that the maximum expected earthquake magnitude for the Manila Trench source zone may reach to the value of Mw = 8.7, and it takes approximately 2 hours for a tsunami from this source zone to hit the Vietnamese coast at the earliest. In this study, we create a worst-case scenario of tsunami earthquake excited by Manila Trench megathrust and assess the impact to the Vietnamese coast. The source parameters are defined based on the models proposed by Wu T-R. et al (2009) and Megawati K. et al (2009). The earthquake magnitude, Mw, is assumed to be 9.3 generated on the Manila Trench. The tsunami propagation is numerically computed by using the COMCOT open source code. We focus the discussion in Central Vietnam coastal regions, and carefully describe the maximum tsunami wave heights around two coastal cities, Da Nang and Nha Trang. In Central Vietnam coast, the maximum tsunami wave high of 18m is observed at the Quang Ngai province coast. The maximum wave height is 10.2m recorded at the coast of Da Nang city and is 8.8m at the coast of Nha Trang city. It might be concluded that the tsunami hazards from Manila Trench source are devastating to Vietnamese coast, especially to the Central Vietnam coast.